A-RPL: Routing Algorithm with the Ability to Support Mobility in Internet of Things Networks - Forough Fazli; Maisam Mansubbassiri; Farshad Babazadeh (مهندسی مخابرات جنوب)
Quick development of technologies and emergence of Internet of Things technology that can link everything environment us is one of the most amazing developments environ the universe. Need to connect and manage fixed and mobile nodes in this type of networks in order to create a proper interaction among them, addition to solving many serious limitations, has caused researchers to address various challenges of this technology. One of the most important challenges is to provide an efficient routing protocol that is able to manage different aspects of network efficiency alongside manages mobility of nodes and dynamic topology of network. RPL (Routing Protocol for Low Power & Lossy Networks) is one of the famous routing protocols is proposed for internet of things networks. This protocol is designed specifically for Internet of Things networks with fixed nodes, so we developed a new routing algorithm called A-RPL to support mobility and solved some challenges caused by mobility. Our algorithm works better than some superior algorithms were proposed in recent years, because they still suffer from various disadvantages, especially for mobile networks